A manual for writers of research papers, theses, and dissertations : Chicago Style for students and researchers - Turabian, Kate L.; Booth, Wayne C.; Colomb, Gregory G.; Williams, Joseph M.; Bizup, Joseph, 1966-; FitzGerald, William T. (2018)
"This new edition of the classic reference work on writing research papers recognizes recent developments in information literacy--including finding, evaluating, and citing a wide range of digital sources--and the evolving use of software for citation management, graphics, and paper format and submission while continuing to reflect best practices for research and writing, as adapted from the most recent editions of The Craft of Research and The Chicago Manual of Style."--Provided by publisher.
Part I: Research and writing. What research is and how researchers think about it -- Defining a project: topic, question, problem, working hypothesis -- Finding useful sources -- Engaging your sources -- Constructing your argument -- Planning a first draft -- Drafting your paper -- Presenting evidence in tables and figures -- Revising your draft -- Writing your final introduction and conclusion -- Revising sentences -- Learning from comments on your paper -- Presenting research in alternative forums -- On the spirit of research -- Source citation. General introduction to citation practices -- Notes-bibliography style: the basic form -- Notes-bibliography style: citing specific types of sources -- Author-date style: the basic form -- Author-date style: citing specific types of sources -- Part III: Style. Spelling -- Punctuation -- Names, special terms, and titles of works -- Numbers -- Abbreviations -- Quotations -- Tables and figures -- Appendix: paper format and submission.
Includes bibliographical references (pages 421-446) and index.
Keywords: Dissertations, Academic -- Handbooks, manuals, etc; Academic writing -- Handbooks, manuals, etc